Theocratically bounded communal self-governance: a pre-modern solution for the modern world? - Rahimi, Haroun (Frontiers in Political Science, 2024)
Shadi Hamid proposes “democratic minimalism” as a system and means of governing and rotating power with no prejudice to substantive ideological outcomes. Democratic minimalism is meant to decouple the question of actualizing an ideal society, even a liberal one that provides maximum freedom for the maximum groups of people, from the mechanism of transferring power between groups with opposing beliefs. I sympathize with Hamid’s arguments. Hamid, I believe, correctly identifies the tension between liberal democracy and Islam in the Muslim world in that Muslims if given the choice may not support liberal policies. He also, I think, rightly concludes that the way to live with this dilemma consists of preserving plurality and the possibility of change through persuasion and thoughtful contestation, and not autocratic leadership. However, I argue, he does not sufficiently problematize the nation-state in his analysis. Drawing on the Islamic tradition, I argue we can make progress in this regard by deconstructing the nation-state to make room for communal self-governance and moral heterodoxies.